Resiprositas Antara Anak Dan Orang Tua Dalam Keluarga Jawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT This case study is conducted to obtain a better understanding about parent care in the household level. This research was carried out in Sriharjo village, Imogiri Subdistrict, Bantul regency, DIY. A child's devotion is not only considered to be a form of respect toward the parents, but also the role and the meaning of the parents in the household. The main question answered in this research is how the child shows his/her devotion towards the parents, the role of the parents in the child's household, and how the parents respond to it. Various ways that have been undertaken by the household to give social security (social guarantee?) is the main focus of this research. This research applied two main methods, the quantitative method and the qualitative one. The qualitative method is applied to obtain a better understanding concerning the child's devotion. The result of this research indicates that the child tries to care for his/ her parents, while the parents try to return the favor by trying to be involved in the household work. Even so, conflicts do occur, such as conflicts between the child and the parents. Devotion enables to harmonize the children-parents relationship. A slight change in the meaning of devotion has also occurred resulting in the children-parents conflicts. The parent feels that the child had not given enough assistance as what had been expected of him/ her. Keywords: parent care -- parent respond .â social security -- conflict. "